Transient epileptic amnesia versus transient global amnesia: aspects of differential diagnosis - L. V. Lipatova; I. V. Sakovsky; M.-B. V. Gadaborshev (Эпилепсия и пароксизмальные состояния)
Transient global amnesia (TGA) and transient epileptic amnesia (TEA) are rare phenomena in clinical practice that manifest as transient cognitive amnestic impairments. Despite the similarity in clinical picture, such conditions are pathogenetically heterogeneous and require different therapeutic approaches. TGA is a clinical syndrome characterized by sudden anterograde amnesia of the event lasting up to 24 hours, lacking focal neurological symptoms, and not prone to recurrence. Mimicking TGA, TEA often occurs manifested as epileptic seizures with impaired awareness of varying duration, including long-term (more than 24 hours), as a variant of focal epilepsy. TEA is characterized by recurrent episodes, combination with other manifestations of epilepsy, and comorbidity with neurodegenerative diseases (dementia). For differential diagnosis, it is necessary to use prolonged video-electroencephalographic monitoring with sleep recording, neuroimaging methods (brain magnetic resonance imaging, positron emission tomography), psychological testing, biochemical examination for markers of neurodegeneration.